Antibiotic dispensation rates among participants in community-driven health research projects in Arctic Canada - Kathleen Williams; Amy Colquhoun; Rachel Munday; Karen J. Goodman; CANHelp Working Group (BMC, 2019)
Abstract Background Community-driven projects that aim to address public concerns about health risks from H. pylori infection in Indigenous Arctic communities (estimated H. pylori prevalence = 64%) show frequent failure of treatment to eliminate the bacterium. Among project participants, treatment effectiveness is reduced by antibiotic resistance of infecting H. pylori strains, which in turn, is associated with frequent exposure to antibiotics used to treat other infections. This analysis compares antibiotic dispensation rates in Canadian Arctic communities to rates in urban and rural populations in Alberta, a southern Canadian province. Methods Project staff collected antibiotic exposure histories for 297 participants enrolled during 2007-2012 in Aklavik, Tuktoyaktuk, and Fort McPherson in the Northwest Territories, and Old Crow, Yukon. Medical chart reviews collected data on systemic antibiotic dispensations for the 5-year period before enrolment for each participant. Antibiotic dispensation data for urban Edmonton, Alberta (average population ~ 860,000) and rural northern Alberta (average population ~ 450,000) during 2010-2013 were obtained from the Alberta Government Interactive Health Data Application. Results Antibiotic dispensation rates, estimated as dispensations/person-years (95% confidence interval) were: in Arctic communities, 0.89 (0.84, 0.94); in Edmonton, 0.55 (0.55, 0.56); in rural northern Alberta, 0.63 (0.62, 0.63). Antibiotic dispensation rates were higher in women and older age groups in all regions. In all regions, the highest dispensation rates occurred for β-lactam and macrolide antibiotic classes. Conclusions These results show more frequent antibiotic dispensation in Arctic communities relative to an urban and rural southern Canadian population.